Case Report: The Successful Treatment of Toxocariasis in a Domestic Cat using Pyrantel Pamoate - Juni Claudia Dami; Luh Putu Eka Damayanti; Soedarmanto Indarjulianto; Yanuartono Yanuartono; Dwi Priyowidodo; Agustina Dwi Wijayanti (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2023)
Toxocariasis is an infectious disease caused by Toxocara sp. in cats that lead to deterioration of the condition and can even cause death, especially in kittens. Pyrantel pamoate is an anthelmintic that is currently being abandoned for toxocariasis. The purpose of this paper is to report the success of toxocariasis treatment in a cat using pyrantel pamoate. Female domestic cat, 3 months old, weighing 1.3 kg suffering diarrhea was used in this study. The cat examined including a physical examination, followed by laboratory examination of fecal and blood samples. The results showed the cat's body condition was thin, eye was dirty, anemic mucous membranes, dull hair/loss, and diarrhea with watery stool consistency. The cat examination revealed the presence of Toxocara sp. egg as much as 2,400 EPG in fecal sample, and the results of blood tests found that the cat had normochromic normocytic anemia. The cat was diagnosed toxocariasis with dubious prognosis. A cat treated with kaolin-pectin with 1-2 ml/kg BW orally 2 times a day for 3 days, multivitamin injection at a dose of 0.5 ml intramuscularly, and the anthelmintic pyrantel pamoate at a dose of 20mg/kg BW orally once. After 28 days of treatment, the cat was declared healthy based on better physical conditions, no diarrhea, no worm eggs in the fecal sample, and did not anemia. It concluded that cats with toxocariasis successfully cured by administering the anthelmintic pyrantel pamoate, so this drug is still recommended for the treatment of toxocariasis in cats.